Preparation and application of flame retardant polyester composites
By adding carbon dots and flame retardants to the polyester and adopting in-situ polymerization or blending, the polyester material has high flame retardant properties, stable thermal properties and fluorescence, solving the flame retardant properties of existing polyester materials. The problem of insufficient is suitable for modern environmental protection requirements and industrial production.
Patent Information
- Application Number
- CN202110363010.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-04-02
AI Technical Summary
The flame retardant performance of existing polyester materials is insufficient, and cannot meet modern environmental protection requirements, extreme oxygen index and vertical combustion indicators, and poor mechanical properties, which limit their application.
By adding carbon dots and flame retardants to the polyester, in-situ polymerization or blending, the carbon dots are uniformly dispersed with the polyester and flame retardants, thereby improving the flame retardancy, mechanical properties and fluorescence of the polyester .
It realizes the high flame retardant performance, stable thermal performance and easy crystallinity of polyester materials, and at the same time imparts the fluorescence of the material, meets modern environmental protection requirements and strict combustion indicators, and is suitable for industrial production.
Smart Images

Figure GDA0005155715950000121 
Figure GDA0005155715950000161 
Figure GDA0005155715950000181
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials, and in particular relates to a method for preparing a polyester composite. Background Art
[0002] Polyester is the most widely used and consumed polymer material. As the earliest linear thermoplastic polymer to achieve industrial application, it has been widely used in the fields of plastic packaging, film and chemical fiber due to its excellent physical and mechanical properties such as high modulus, high strength and high elasticity. The application of polyester materials in the fields of automobiles, industrial and civil construction, household goods, electronic appliances, etc. has brought convenience to people's lives. However, because its oxygen index is generally only 21% to 22%, it is a fusible and flammable fiber, which brings potential unsafe factors to people's lives and property. Therefore, it is imperative to study the flame retardancy of polyester.
[0003] Polyethylene terephthalate (PET) is the most representative of polyesters, which is an aromatic saturated polyester. PET fiber is favored by textile professionals and consumers due to its excellent properties such as high strength, high modulus, good resilience, good abrasion resistance, low water absorption, and strong chemical stability. With the development of the PET industry, the demand for functionalization of PET fiber has become more obvious. Therefore, it is more urgent to improve the flame retardant properties of PET.
[0004] In the prior art, flame retardants are compounded with polyester to improve the ability of polyester to resist combustion and achieve a long-term flame retardant effect. Phosphorus flame retardants occupy an important position in flame retardants. They not only overcome the defects of halogen-containing flame retardants that produce large smoke and emit toxic and corrosive gases, but also improve the shortcomings of inorganic flame retardants that seriously affect the physical and mechanical properties of materials due to high addition, and achieve high flame retardancy, low smoke, low toxicity, and no abrasive gas generation, which has great development potential and space. However, due to some defects of phosphorus flame retardants themselves, such as poor compatibility, imperfect surface treatment technology, organic phosphorus systems are mostly liquid, highly volatile, large smoke, poor thermal stability, etc., their application has been limited.
[0005] At present, there are numerous studies on the preparation of flame-retardant polyester composites by combining phosphorus-based flame retardants with polyesters. However, due to the defects of the flame retardants themselves, the resulting materials do not meet today's environmental protection requirements or do not meet the limiting oxygen index and vertical combustion index tests, and have poor mechanical properties, which seriously limits their application.
[0006] In view of the above reasons, developing a flame-retardant polyester composite with good flame retardancy, low price and environmental protection remains the focus of polyester research. Summary of the invention
[0007] In order to overcome the above problems, the inventors have conducted intensive research on polyester composites and developed a polyester composite with good flame retardancy, stable thermal properties and easy crystallization. The composite includes polyester, carbon dots and flame retardant. The addition of carbon dots can not only improve the flame retardancy of polyester but also give the polyester composite fluorescent properties, so that it has the potential to prepare flame retardant fibers and fluorescent anti-counterfeiting fibers at the same time. The carbon dots act as crosslinking points when the polymerization system burns, which increases the amount of residual carbon in the system and reduces the rate of thermal weight loss, effectively inhibiting heat transfer and improving flame retardancy. The present invention uses in-situ polymerization or blending to add carbon dots and flame retardants to polyester. Since the carbon dots are highly compatible with polyester, they are beneficial to improving the mechanical properties of the matrix and have both flame retardancy and fluorescence, providing a new development idea for polymer flame retardancy and enhancement modification, thereby completing the present invention.
[0008] Specifically, the purpose of the present invention is to provide the following aspects:
[0009] In a first aspect, application of carbon dots as polymer flame retardants is provided.
[0010] In a second aspect, a flame retardant composition is provided, which includes carbon dots and a flame retardant, and the flame retardant includes any one or more of a halogen flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, and an inorganic hydroxide flame retardant.
[0011] In a third aspect, a flame retardant polymer is provided, wherein the flame retardant polymer comprises carbon dots and a flame retardant, wherein the carbon dots and the flame retardant are preferably copolymerized in the flame retardant polymer by in-situ polymerization.
[0012] In a fourth aspect, a flame-retardant polyester composite is provided, wherein the flame-retardant polyester composite comprises polyester, carbon dots and a flame retardant, wherein the polyester comprises any one or more of polyethylene terephthalate, polybutylene terephthalate and polytrimethylene terephthalate.
[0013] In a fifth aspect, a method for preparing a flame retardant polyester composite is provided, the method comprising:
[0014] Step 1, mixing carbon dots with prepolymer monomers to carry out esterification reaction;
[0015] Step 2, subjecting the reaction solution obtained by the esterification reaction in step 1 to a condensation polymerization reaction.
[0016] The beneficial effects of the present invention include:
[0017] (1) The polyester composite provided by the present invention utilizes the fluorescence of carbon dots themselves to give the polyester composite fluorescence, and has the potential to prepare fluorescent anti-counterfeiting fibers. At the same time, as cross-linking points in the polymerization system, it effectively improves the crystallinity of polyester and gradually increases the residual carbon content of the system, effectively inhibiting heat transfer.
[0018] (2) The polyester composite provided by the present invention has good flame retardancy, stable thermal properties and is easy to crystallize. The addition of carbon dots does not change the thermal degradation process of polyester, but instead increases its residual carbon content and flame retardancy.
[0019] (3) The preparation method of the polyester composite provided by the present invention in situ copolymerizes the carbon dots and the flame retardant in the polyester, which is conducive to the full mixing of the reactants and enhances the compatibility between the reactants. The co-doping of the carbon dots and the flame retardant forms a superposition effect, and the thermal insulation effect is further enhanced, thereby reducing the production cost of the polyester composite, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 -a shows the TEM characterization of carbon dots prepared in an embodiment of the present invention;
[0021] Figure 1 -b shows the particle size distribution diagram of carbon dots prepared in Example 1 of the present invention;
[0022] Figure 2 The fluorescence spectrum of the carbon dots obtained in Example 1 of the present invention when the excitation light wavelength is 320 nm is shown;
[0023] Figure 3 The thermogravimetric change curve of Experimental Example 1 is shown;
[0024] Figure 4 The DSC curve of Experimental Example 2 is shown;
[0025] Figure 5 The cone calorimetry test curve of Experimental Example 3 is shown;
[0026] Figure 6 FTIR graph of Experimental Example 4 is shown;
[0027] Figure 7 The SEM photograph of Experimental Example 5 is shown;
[0028] Figure 8 The fluorescence performance test spectrum of Experimental Example 6 is shown. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.
[0030] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0031] The first aspect of the present invention aims to provide an application of carbon dots as polymer flame retardants.
[0032] It is worth noting that with the rapid development of nanotechnology, nanomaterials have gradually been applied to the field of flame retardancy. Therefore, nano flame retardancy has become an important direction in the field of flame retardancy. Carbon nanomaterials are widely used in the flame retardant modification of polymers due to their abundant sources, diverse preparation methods, and excellent flame retardant properties. Among them, carbon nanotubes, graphene, nano carbon black and their derivatives have been used in polymer flame retardancy and have achieved many beneficial effects. However, the corresponding flame retardant composites perform poorly in the limiting oxygen index and vertical burning tests and cannot pass the corresponding tests. Moreover, these carbon nanomaterials have the problem of uneven dispersion during the addition process, which has an adverse effect on the mechanical properties of the matrix material.
[0033] As a zero-dimensional carbon nanomaterial, carbon dots are a new type of nanoscale fluorescent material mainly composed of carbon elements. Their essential characteristics are that the size of at least one dimension is less than 10nm and they have the property of photoluminescence. As a new member of the carbon material family, carbon dots not only maintain the advantages of carbon materials such as low toxicity and good biocompatibility, but also have the advantages of resistance to photobleaching, adjustable fluorescence emission, easy functionalization, wide source of raw materials, and easy large-scale synthesis. In addition, the surface of carbon dots usually has many functional groups, such as carbonyl, hydroxyl and carboxyl, which makes it easy to combine with flame-retardant polymers to achieve functionalization. In other words, carbon dots have good compatibility with polymer flame retardants in terms of structure.
[0034] The inventors have proved through practice that the application of carbon dots to polymer flame retardants will not affect the original properties of polymer flame retardants, but will improve their properties, such as flame retardancy and mechanical properties, and can also give polymer flame retardants fluorescence, which has great application potential in polymer flame retardants.
[0035] According to the present invention, in order to optimize the compatibility of carbon dots with flame retardant polymers, the carbon dots are preferably carbon quantum dots, and the particle size thereof is less than 100 nm, preferably 2 to 60 nm, and more preferably 4 to 20 nm.
[0036] According to the present invention, the excitation wavelength of the carbon dots is 280-600 nm, preferably 300-480 nm, more preferably 320-400 nm; the emission wavelength is 360-800 nm, preferably 400-700 nm, more preferably 420-600 nm.
[0037] A second aspect of the present invention is to provide a flame retardant composition, which comprises carbon dots and a flame retardant.
[0038] According to the present invention, the flame retardant includes any one or more of a halogen flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, and an inorganic hydroxide flame retardant.
[0039] In a further preferred embodiment, the flame retardant is a phosphorus flame retardant, including reactive phosphorus flame retardants and additive phosphorus flame retardants. The plasticizing function of the phosphorus flame retardant can improve the flow processability of the composite during molding, inhibit the residue after combustion, and produce less toxic and corrosive gases than halogen flame retardants. In addition, the phosphorus flame retardant has little effect on light stability or the effect of light stabilizers, and has the effect of preventing re-ignition.
[0040] The inventors have found that the flame retardant effect of carbon dots is limited, but the synergistic effect with phosphorus-based flame retardants can enhance the flame retardancy of the flame retardant composition, and the carbon dots will form a superposition effect, thereby enhancing the heat insulation effect.
[0041] According to the present invention, the weight ratio of the carbon dots to the flame retardant is (0.2-2):(0.1-20), preferably (0.8-1.5):(1-15), and more preferably (0.9-1.2):(1.7-5.0).
[0042] In the present invention, as the weight ratio of carbon dots in the flame retardant composition increases, the fluorescence, mechanical properties and thermal insulation effects are significantly enhanced. Excessive carbon dots lead to a decrease in the mechanical properties of the flame retardant composition, which may be due to stress concentration caused by excessive addition of carbon dots.
[0043] The third aspect of the present invention is to provide a flame retardant polymer comprising carbon dots and a flame retardant.
[0044] According to the present invention, carbon dots and flame retardants are copolymerized in the flame retardant polymer by in-situ polymerization, wherein the in-situ polymerization is beneficial to uniformly disperse the carbon dots and flame retardants in the flame retardant polymer, thereby further improving the flame retardancy, mechanical properties, fluorescence and other properties of the flame retardant polymer.
[0045] In a fourth aspect of the present invention, the object is to provide a flame retardant polyester composite, wherein the composite has both flame retardancy and fluorescence, wherein the limiting oxygen index reaches above 26%, or even above 28%, for example, 34%, the vertical combustion grade is V-0, and the fluorescence intensity reaches 2×10 4 Above, preferably 1×10 5 More than 1×10 6 In addition, the composite has excellent mechanical properties, and its elongation at break is above 6.0%, preferably above 7.2%, more preferably above 7.6%, for example 8.4%.
[0046] In the present invention, the composite includes polyester, carbon dots and a flame retardant.
[0047] The weight percentage of the polyester, carbon dots and flame retardant is (85-95): (0.01-5): 5, preferably (88-93): (0.1-3): 5, and more preferably (92-93): (0.2-2): 5.
[0048] According to the present invention, the weight of the carbon dots affects the flame retardancy and mechanical properties of the composite. When the weight percentage of polyester, carbon dots and flame retardant is (85-95): (0.01-5): 1, the performance of the composite is optimal.
[0049] According to the present invention, the polyester used as the base material of the composite has the characteristics of wide sources, including any one or more of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), and polycarbonate (PC), preferably PET.
[0050] In the present invention, the PET has the characteristics of high strength, stiffness, wear resistance and good wearing performance.
[0051] In the present invention, the flame retardant includes any one or more of halogen flame retardants, phosphorus flame retardants, nitrogen flame retardants, silicon flame retardants, and inorganic hydroxide flame retardants, preferably phosphorus flame retardants, including reactive phosphorus flame retardants and additive phosphorus flame retardants, more preferably reactive phosphorus flame retardants.
[0052] In the present invention, the reactive phosphorus-based flame retardant achieves flame retardancy by reacting flame retardant monomers or flame retardant groups into the main chain or side chain of polyester, has little effect on the comprehensive properties of polyester, and has a more durable flame retardant effect on the composite.
[0053] In a further preferred embodiment, the flame retardant is a reactive organophosphorus flame retardant, such as bis(p-carboxyphenyl)phenyl phosphine oxide (BCPPO), 2-carboxyethylphenylphosphinic acid (CEPPA), etc. On the one hand, the organophosphorus flame retardant has the effect of promoting the carbonization of the polymer and promoting the carbonization of the polyester during the combustion process. On the other hand, since it does not contain halogen elements, it is very environmentally friendly.
[0054] The fifth aspect of the present invention aims to provide a method for preparing a flame retardant polyester composite, which is prepared by in-situ polymerization, and the method comprises:
[0055] Step 1: Mix the carbon dots with the prepolymer monomers and perform an esterification reaction.
[0056] In step 1, the carbon dots are preferably carbon quantum dots, with a particle size of less than 100 nm, preferably 2.0 to 60.0 nm, more preferably 4 to 20 nm; and a fluorescence intensity of 2×10 4 Above, preferably 1×10 5 More than 1×106 or above; the excitation wavelength is 280 to 600nm, preferably 300 to 480nm, more preferably 320 to 400nm; the emission wavelength is an emission wavelength of 360 to 800nm, preferably 400 to 700nm, more preferably 420 to 600nm.
[0057] According to the present invention, the carbon dots are preferably prepared by gelatin via a hydrothermal method. The TEM characterization of the carbon dots prepared in the preferred manner is as follows: Figure 1 -a as shown.
[0058] In the present invention, the gelatin is not limited to any gelatin on the market, and includes any one or more of edible gelatin, medicinal gelatin, and industrial gelatin, preferably industrial gelatin.
[0059] In the present invention, the raw materials of industrial gelatin are mostly tanned leather scraps, which contain heavy metals such as Cr (VI) and are difficult to reuse and are discarded, causing environmental pollution. Therefore, the present invention uses industrial gelatin to prepare carbon dots.
[0060] In the present invention, the hydrothermal method refers to a method of placing the precursor gelatin in an autoclave aqueous solution for hydrothermal reaction, and then separating and drying to obtain carbon dots. This method is green, simple and fast.
[0061] Furthermore, the precursor gelatin is placed in an aqueous solution in a polytetrafluoroethylene-lined reactor for hydrothermal reaction, and then centrifuged and freeze-dried to obtain carbon dots.
[0062] Wherein, the weight ratio of gelatin to water is 1:(5-50), preferably 1:(10-30), and more preferably 1:(20-25).
[0063] According to the present invention, the reaction temperature of the hydrothermal method is 180-300°C, preferably 210-260°C, more preferably 220-250°C, for example 240°C.
[0064] In the present invention, as the reaction temperature increases, the fluorescence intensity gradually increases. When the temperature reaches above 250°C, especially 300°C, the fluorescence intensity is significantly weakened. The inventors believe that this may be because the carbon points generated by gelatin during the carbonization process agglomerate, resulting in a weakening of the fluorescence intensity.
[0065] According to the present invention, the reaction time of the hydrothermal method is 12 to 48 hours, preferably 16 to 36 hours, more preferably 22 to 28 hours, for example 24 hours.
[0066] In the present invention, as the reaction time increases, the fluorescence intensity also increases. When the reaction time exceeds 48 hours, the fluorescence intensity increases very little and basically tends to be stable. In order to shorten the reaction time, the preferred reaction time is 12 to 48 hours.
[0067] In step 1, the prepolymer monomers include alcohol compounds and carboxylic acid compounds.
[0068] According to a preferred embodiment, the alcohol compound includes monoalcohols and polyols, preferably polyols, such as ethylene glycol, glycerol, sorbitol, etc., more preferably ethylene glycol.
[0069] In the present invention, the polyester compound prepared from structurally symmetrical ethylene glycol has obvious crystallinity.
[0070] According to a preferred embodiment, the carboxylic acid compound includes aliphatic carboxylic acid and aromatic carboxylic acid, preferably aromatic carboxylic acid, such as terephthalic acid and 5-methyl-isophthalic acid, more preferably terephthalic acid, which is easy to be crystallized and purified.
[0071] According to a preferred embodiment, a flame retardant and a catalyst are also added in step 1.
[0072] In the prior art, there are many kinds of compounds that can catalyze the esterification reaction and polycondensation reaction of polyester, which almost cover all elements except halogen elements and inert elements. However, the main research is on compounds such as antimony, germanium, and titanium. Antimony catalysts have moderate activity and low price, and are most commonly used in the polyester industry.
[0073] In the present invention, the antimony-based catalyst is preferably selected from any one or more of antimony acetate, antimony oxide, and ethylene glycol antimony. Considering factors such as catalyst performance and price, antimony oxide is more preferably used as the catalyst.
[0074] According to the present invention, the esterification reaction temperature is 220-270°C, preferably 240-260°C, and more preferably 250-255°C.
[0075] In the present invention, increasing the temperature will slightly increase the esterification reaction rate. Since the molecular structure of the phosphorus-based flame retardant such as CEPPA in the present invention is relatively complex, the steric hindrance is large, and the mutual collision and contact between the groups are more difficult, the esterification reaction temperature is controlled at 220-270°C.
[0076] In the present invention, since an excessively long esterification reaction time leads to a decrease in the conversion rate of the carboxylic acid compound, the reaction time is controlled to be 0.2 to 2 hours, preferably 0.5 to 1 hour, and more preferably 0.8 to 1 hour.
[0077] In a preferred embodiment, the step 1 comprises the following steps:
[0078] Step 1-1, dissolving carbon dots in an alcohol compound to obtain a premix;
[0079] Step 1-2, adding a carboxylic acid compound, a flame retardant and a catalyst to the premix obtained in step 2-1 to carry out an esterification reaction.
[0080] Wherein, in step 1-1, the concentration of the carbon dots dissolved in the alcohol compound is 5-15%, preferably 7-12%, and more preferably 8-9%.
[0081] Step 2, subjecting the reaction solution obtained by the esterification reaction in step 1 to a condensation polymerization reaction.
[0082] According to a preferred embodiment, before the polycondensation reaction, an antioxidant and an anti-hydrolysis agent are added to the reaction solution obtained in step 1. In addition, in order to ensure the complete esterification reaction, a small amount of alcohol compound is preferably added to the reaction solution.
[0083] Among them, polyester usually ages rapidly under the action of light, oxygen and heat, resulting in a decrease in strength, stiffness and toughness, and even discoloration, scratches, and a decrease in surface gloss, affecting the performance of polyester materials. Antioxidants can inhibit the breakage of molecular chains and extend the performance of polyester materials.
[0084] The antioxidant of the present invention includes any one or more of phosphites, thiodipropionates and thiols, preferably phosphites, such as triphenyl phosphite, dioctadecyl pentaerythritol diphosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and more preferably triphenyl phosphite.
[0085] In the present invention, the phosphite has good antioxidant effect and is a halogen-free environmentally friendly antioxidant, especially triphenyl phosphite, which is not only green and environmentally friendly, but also has certain flame retardancy.
[0086] According to the present invention, in a humid and warm environment, water molecules will destroy the macromolecular chains of polyester, causing hydrolysis reaction, thereby causing its degradation. In order to effectively prevent the occurrence of hydrolysis, an anti-hydrolysis agent is added.
[0087] In the present invention, the anti-hydrolysis agent includes any one or more of carbodiimide, oxazoline compounds, and epoxy compounds, preferably epoxy compounds, such as anti-hydrolysis agent 1010.
[0088] In the present invention, the anti-hydrolysis agent 1010 has high activity and can effectively capture the carboxyl groups generated by polymer hydrolysis to prevent the further progress of the hydrolysis reaction, thereby effectively inhibiting the degradation of the mechanical properties of the polyester material caused by hydrolysis and greatly extending the service life of the product.
[0089] In step 2, the polycondensation reaction is divided into two stages:
[0090] Low vacuum stage: reaction temperature is 230-300°C, reaction time is 0.1-6h, and system pressure is controlled at -80-120kPa;
[0091] High vacuum stage: reaction temperature is 240-300°C, reaction time is 0.2-10h, and system pressure is controlled at -90--112kPa.
[0092] According to the present invention, the higher the temperature, the faster the reaction speed, but too high a temperature will cause thermal degradation of the polymer. The polycondensation reaction of the present invention first reacts at a relatively low temperature, and as the reaction proceeds, the viscosity of the material melt increases, and then the temperature is raised again, which is conducive to the diffusion and escape of the generated small molecular byproducts.
[0093] In a further preferred embodiment, the polycondensation reaction stage control conditions are as follows:
[0094] Low vacuum stage: reaction temperature is 240-290°C, reaction time is 0.3-3h, and system pressure is controlled at -90--110kPa;
[0095] High vacuum stage: reaction temperature is 260-290°C, reaction time is 1-6h, and system pressure is controlled at -95--106kPa.
[0096] In a further preferred embodiment, the polycondensation reaction stage control conditions are as follows:
[0097] Low vacuum stage: reaction temperature is 270-275°C, reaction time is 0.5-1h, and system pressure is controlled at -99.5-100.00kPa;
[0098] High vacuum stage: reaction temperature is 276-278°C, reaction time is 2.5-3h, and system pressure is controlled at -100--102kPa.
[0099] According to the present invention, in the method for preparing a flame-retardant polyester composite, the weight ratio of the alcohol compound, the carboxylic acid compound, the flame retardant, the catalyst, the antioxidant and the anti-hydrolysis agent is (300-600): (800-1200): (10-60): (0.01-2): (0.1-5): 1, preferably (400-500): (900-1050): (30-50): (0.1-1): (0.5-2): 1, and more preferably (430-450): (980-1010): (40-43): (0.2-0.5): (0.9-1.2): 1.
[0100] Example
[0101] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0102] The sources of the reagents used in the following examples are as follows:
[0103]
[0104] Example 1
[0105] (1) Preparation of carbon dots
[0106] Weigh 1.0 g of gelatin and place it in a 100 mL clean beaker. Use 20 mL of deionized water as the solvent, stir it evenly and transfer it to a 50 mL polytetrafluoroethylene-lined reactor. Then put the reactor into a hot air oven and react at 240 ° C for 24 hours. Then let the reactor cool naturally to room temperature to obtain a brown carbon solution. Finally, centrifuge and freeze-dry to obtain carbon dots. Its TEM morphology is shown in the figure. Figure 1 As shown in Figure 2, the carbon dots are spherical in structure, evenly dispersed and without agglomeration. Figure 1 -b is the particle size distribution diagram corresponding to the TEM image. The results show that the particle size of the carbon dots is between 4.3 and 8.8 nm, with an average particle size of 6.2 nm. The fluorescence spectrum of the emitted light when the excitation wavelength of the prepared carbon dots is 320 nm is shown in Figure 2 As shown, its fluorescence intensity reaches 2×10 6 .
[0107] (2) Take 12.0 g of the carbon dots (CPDs) prepared in step (1) and dissolve it in 282 mL of EG to obtain an EG-CPDs solution. Add 700 g of PTA, 30 g of CEPPA, 0.28 g of Sb2O3 and the EG-CPDs solution into a polymerization reactor and react in a heat preservation environment at 240°C for 1 hour to obtain the oligomer BHET.
[0108] (3) After the reaction in step (2) was completed, 0.7 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then a polymerization reaction was carried out. The polymerization reaction conditions were as follows:
[0109] Low vacuum stage: reaction temperature is 270-275°C, reaction time is 0.5h, and system pressure is controlled at -100.80kPa;
[0110] High vacuum stage: reaction temperature is 276-278°C, reaction time is 3h, and system pressure is controlled at -101.00kPa.
[0111] After the reaction is completed, a PET composite is obtained, and the carbon point content in the obtained PET composite is 1.5 wt %.
[0112] Example 2
[0113] The PET composite was prepared in a similar manner to Example 1, except that:
[0114] Take 2.0g carbon dots (CPDs) and dissolve it in 282mL EG to obtain EG-CPDs solution. Add 700g PTA, 30g CEPPA, 0.28g Sb2O3 and EG-CPDs solution into the polymerization reactor and react at 240℃ for 1h to obtain the oligomer BHET.
[0115] After the reaction was completed, 0.7 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then the polymerization reaction was carried out.
[0116] The carbon dot content in the finally prepared PET composite is 0.25wt%.
[0117] Example 3
[0118] The PET composite was prepared in a similar manner to Example 1, except that:
[0119] Take 4.0g carbon dots (CPDs) and dissolve them in 282mL EG to obtain EG-CPDs solution. Add 700g PTA, 30g CEPPA, 0.28g Sb2O3 and EG-CPDs solution into the polymerization reactor and react at 240℃ for 1h to obtain the oligomer BHET.
[0120] After the reaction was completed, 0.70 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and the polymerization reaction was further carried out.
[0121] The carbon dot content in the finally prepared PET composite is 0.50wt%.
[0122] Example 4
[0123] The PET composite was prepared in a similar manner to Example 1, except that:
[0124] Take 6.0g carbon dots (CPDs) and dissolve them in 282mL EG to obtain EG-CPDs solution. Add 700g PTA, 30g CEPPA, 0.28g Sb2O3 and EG-CPDs solution into the polymerization reactor and react at 240℃ for 1h to obtain the oligomer BHET.
[0125] After the reaction was completed, 0.7 g of anti-hydrolysis agent 1010, 0.65 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and the polymerization reaction was further carried out.
[0126] The carbon dot content in the finally prepared PET composite is 0.75wt%.
[0127] Example 5
[0128] The PET composite was prepared in a similar manner to Example 1, except that:
[0129] Take 8.0g carbon dots (CPDs) and dissolve them in 282mL EG to obtain EG-CPDs solution. Add 700g PTA, 30g CEPPA, 0.28g Sb2O3 and EG-CPDs solution into the polymerization reactor and react at 240℃ for 1h to obtain the oligomer BHET.
[0130] After the reaction was completed, 0.70 g of anti-hydrolysis agent 1010, 0.65 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and the polymerization reaction was further carried out.
[0131] The carbon dot content in the finally prepared PET composite was 1.00 wt%.
[0132] Example 6
[0133] The PET composite was prepared in a similar manner to Example 1, except that:
[0134] Take 16.0g carbon dots (CPDs) and dissolve them in 282mL EG to obtain EG-CPDs solution. Add 700g PTA, 30g CEPPA, 0.28g Sb2O3 and EG-CPDs solution into the polymerization reactor and react at 240℃ for 1h to obtain the oligomer BHET.
[0135] After the reaction was completed, 0.7 g of anti-hydrolysis agent 1010, 0.65 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and the polymerization reaction was further carried out.
[0136] The carbon dot content in the finally prepared PET composite was 2.00 wt%.
[0137] Comparative Example
[0138] Comparative Example 1
[0139] The PET composite was prepared in a similar manner to Example 1, except that carbon dots and CEPPA were not added.
[0140] Comparative Example 2
[0141] The PET composite was prepared in a similar manner to Example 1, except that no carbon dots were added.
[0142] Experimental example
[0143] Experimental Example 1 Thermal Stability Test
[0144] The PET composites obtained in Examples 1-6 and Comparative Examples 1-2 were tested using a 209F 1 thermogravimetric analyzer. The test conditions were a nitrogen atmosphere, a temperature range of 30 to 800°C, and a heating rate of 10°C / min. The thermogravimetric changes were as follows: Figure 3 As shown, Figure 3 -a shows the carbon residue variation curve with increasing temperature, and 3-b shows the mass reduction variation curve with increasing temperature; accordingly, the test data are shown in Table 1:
[0145] Table 1 Thermogravimetric test results
[0146]
[0147] Combination Figure 3 As can be seen from Table 1, after adding CEPPA, the T 5wt% The temperature of the PET composite prepared in Comparative Example 1 was reduced from 389.63°C to 380.59°C. After adding carbon dots, the temperature 5wt% Still maintained around 380℃.
[0148] Compared with T max It can be seen that T max There is no obvious change, indicating that the addition of carbon dots does not change the thermal degradation process of PET. It is worth noting that the addition of carbon dots significantly increases the carbon residue of the matrix at 700°C, especially after adding 2.00% carbon dots in Example 6, the carbon residue increases from 7.50% in Comparative Example 1 to 12.1%, an increase of 61.3%. The increase in the amount of carbon residue can better form a shielding layer in the condensed phase, isolate oxygen and heat, and inhibit further degradation of the internal material.
[0149] Experimental Example 2 Thermal Performance Test
[0150] 6-8 mg of the PET composite obtained in the above Examples 1-6 and Comparative Examples 1-2 were taken respectively, and a Q2000 differential scanning calorimeter was used, with nitrogen as the protective gas, and the test conditions were set to a pressure of 0.1 MPa, a temperature program from 30°C to 300°C, a temperature increase rate of 10°C / min, and a temperature decrease rate of 10°C / min. The measured DSC curve of the PET composite is as follows: Figure 4 The test data is shown in Table 2:
[0151] Table 2DSC data
[0152] sample <![CDATA[T g / ℃]]> <![CDATA[T c / ℃]]> <![CDATA[T m / ℃]]> Example 1 62 151 228 Example 2 63 164 230 Example 3 67 163 229 Example 4 60 158 228 Example 5 70 154 229 Example 6 67 150 227 Comparative Example 1 64 209 245 Comparative Example 2 69 153 219
[0153] Depend on Figure 4 From the data analysis of Table 3 and Table 4, it can be seen that the melting point of the PET compound prepared in Comparative Example 2 is lower than that of the PET compound prepared in Comparative Example 1, and the melting points of the PET compounds prepared in Examples 1-6 are between those of the PET compounds prepared in Comparative Example 1 and Comparative Example 2. This is because, relative to the PET compound in Comparative Example 2, the carbon dots in the PET compounds prepared in Examples 1-6 serve as cross-linking points in the polymerization system, which is beneficial to increase the viscosity and crystallinity, thereby increasing the melting point.
[0154] Depend on Figure 4 b and Table 3, the crystallization temperature of the PET compound prepared in Comparative Example 2 is lowered, and crystallization becomes difficult. The crystallization temperature of the PET compound prepared in Examples 1-6 is between that of the PET compound prepared in Comparative Example 1 and Comparative Example 2, and when the mass fraction of CDs reaches 1%, the crystallization temperature tends to be stable.
[0155] Experimental Example 3 Flame retardant performance test
[0156] Experimental Example 3-1 Limiting Oxygen Index (LOI) Test
[0157] The PET compounds obtained in Examples 1-6 and Comparative Examples 1-2 were prepared into test specimens with a size of 80 mm×6.5 mm×3 mm using a Haake MiniJet micro-sample forming instrument. The LOI values of the samples were determined using a Dynisco limiting oxygen index analyzer with reference to GB / T 2406-93 "Plastic Combustion Performance Test Method Oxygen Index Method".
[0158] Experimental Example 3-2 Vertical Burning (UL-94) Test
[0159] The PET compounds obtained in Examples 1-6 and Comparative Examples 1-2 were prepared into test specimens with a size of 130 mm×13 mm×3 mm using a Haake MiniJet micro-sample forming instrument. The vertical combustion performance of the flame retardant copolymer was tested using a CZF-3 horizontal combustion tester from Nanjing Jiangning District Analytical Instrument Factory with reference to the test standard GB / T2408-2008 "Horizontal and vertical methods for testing the combustion performance of plastics".
[0160] The test results of Experimental Example 2 and Experimental Example 3 are shown in Table 3:
[0161] Table 3 LOI and UL-94 test results
[0162]
[0163]
[0164] The experimental results show that when the carbon dot content is small, the LOI of the PET composite prepared in Example 1 is smaller than that of the PET composite prepared in Example 1. As the carbon dot content increases, the LOI value of the PET composite gradually increases. When the carbon dot addition amount reaches 1% and 1.5%, the LOI reaches 34, but when the carbon dot addition amount increases to 2%, the LOI value decreases. The UL-94 test results of the prepared PET composites with different carbon dot contents are all V-0 grades. In summary, within a certain addition amount range (0.75%-1.5%), the addition of CDs is beneficial to the improvement of the flame retardant properties of the PET composite.
[0165] Experimental Example 3-3 Cone Calorimetry (CONE) Test
[0166] The PET compounds obtained in Examples 1-6 and Comparative Examples 1-2 were prepared into test specimens with a size of 100 mm × 100 mm × 3 mm using a Haake MiniJet micro-sample forming instrument. Referring to the test standard ISO 5660-1 "Reaction to fire test heat release, smoke production and mass loss rate Part 1: Heat release rate (cone calorimeter method)", the flame retardant copolymer was tested using the British Fire Testing Technology Ltd standard cone calorimeter (FTT Standard Corn Calorimeter), and the parameter radiation power was set to 50KW / m 2 , Figure 5 Table 4 shows the cone calorimetry test results of the PET composites obtained in Examples 1-6 and Comparative Examples 1-2.
[0167] Table 4 Cone calorimetry test results
[0168]
[0169]
[0170] Depend on Figure 5 -aHRR shows that the PET composites with 0.75%, 1.00%, and 1.50% CDs have better flame retardant properties, and the same rule also exists in the 5-bTHR graph.
[0171] As shown in Table 4, the average ignition time of PET is 51s. After adding flame retardant and carbon dots, the ignition time of PET composite is significantly prolonged, indicating that the addition of carbon dots makes the ignition of PET composite system difficult and can effectively reduce the speed of flame spread. The maximum heat release rate of PET composite prepared in comparative example 1 is 915.85kW / m 2 , after adding CEPPA and carbon dots, the peak value of heat release rate is significantly reduced.
[0172] Table 4 and Figure 5 Combined, the flame retardant properties of polymers can be better evaluated. The greater the total heat release and the peak value of the heat release rate, the greater the fire hazard formed by the material. In summary, the ignition time of the PET composite doped with carbon dots increases, the peak value of the heat release rate decreases, the average heat release rate decreases, and the total heat release decreases. This shows that the addition of CDs can improve the flame retardant properties of PET using CEPPA alone.
[0173] Experimental Example 3-4 Residual Carbon Structure Characterization Test
[0174] The residual carbon structure of the PET composites prepared in Comparative Examples 1-2 and Example 1 was characterized by Fourier transform infrared spectroscopy (FTIR) with a scanning range of 4000-400 cm -1 ,like Figure 6 As shown, the PET compounds prepared in Comparative Example 2 and Example 1 both contain hydrocarbon groups, while the residual carbon of the PET compound prepared in Comparative Example 1 does not contain CH stretching vibration peaks, which shows that the degradation of the PET compounds prepared in Comparative Example 2 and Example 1 has been inhibited to a certain extent. -1 The absorption peaks are characteristic absorption peaks of carbonyl and ester groups, and the peaks are enhanced after adding CEPPA, indicating that COC structure and POC structure are formed. When the carbon dots are copolymerized, the whole is displaced, forming a superposition effect and enhancing the barrier effect.
[0175] Experimental Example 3-5 Characterization of residual carbon morphology
[0176] The residual carbon morphology of the PET composites prepared in Comparative Examples 1-2 and Example 1 was observed using a JSM-6360 scanning electron microscope from JEOL Ltd. The vacuum degree was 9.63×10-3Pa, the voltage was adjusted to 8kV, and the scale was 50μm. The SEM characterization was as follows: Figure 6 As shown,
[0177] 6-a is the carbon residue image of comparative example 1, 6-b is the carbon residue image of comparative example 2, and 6-c is the carbon residue image of embodiment 1. It can be clearly seen that a carbon residue structure with tiny holes is formed in 6-a, indicating that the heat insulation effect of the effective barrier layer is low. When CEPPA is added (corresponding to 6-b), the holes in the carbon layer become larger, indicating that CEPPA is mainly meteorological flame retardant. However, after adding carbon dots (corresponding to 6-c), a dense carbon layer with small and few holes is obtained on the surface. This is because the carbon dots are evenly dispersed in the flame retardant system and improve the carbonization and barrier effect of doped CEPPA.
[0178] Experimental example Mechanical properties test
[0179] Before testing, the PET composites obtained in Examples 1-6 and Comparative Examples 1-2 were prepared using a Haake MiniJet micro-sample forming instrument to prepare dumbbell-shaped test specimens with a middle handle of 30 mm×4 mm×2 mm in size. The tensile strength, elastic modulus and elongation at break of the specimens were then tested using an electronic universal strength tester. The results are shown in Table 5:
[0180] Table 5 Mechanical properties test results
[0181]
[0182] From the tensile strength test results, it can be seen that with the increase of carbon point addition, the tensile strength of the flame retardant copolymer increases, but when the tensile strength value rises to a certain extent, the value begins to decrease. The test results show that when the carbon point addition reaches 0.75% (corresponding to Example 4), the tensile strength is 59.77MPa and the elastic modulus reaches 1308.45MPa. This shows that a certain amount of carbon point addition is beneficial to improving the mechanical properties of flame retardant polyester, but when the carbon point addition reaches 2% (corresponding to Example 6), the tensile modulus, elastic modulus, and elongation at break all decrease, which may be because the excessive addition of carbon points causes stress concentration.
[0183] Experimental Example 5 Fluorescence Performance Test
[0184] The fluorescence emission spectra of the PET composites obtained in Examples 1-6 and Comparative Examples 1-2 were characterized using a multifunctional fluorescence spectrometer (model FS5, Techcomp (China) LTD). The excitation light used for the fluorescence emission spectra of FRPET-CDs was 320 nm, and the slit widths of the incident light and the emission light were 2 mm and 1 mm, respectively. Figure 8 As shown in the emission spectrum, the PET composite prepared in Comparative Example 1 has almost no fluorescence, and the fluorescence of PET added with CEPPA (Comparative Example 2) is also very weak. As the content of carbon dots increases, the fluorescence intensity of the PET composite gradually increases, and the fluorescence intensity is the highest when the carbon dots are added in an amount of 1.5% (Example 1).
[0185] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a flame retardant polyester composite, characterized in that: (1) Preparation of carbon dots 1.0 g of gelatin was weighed and placed in a 100 mL clean beaker, and 20 mL of deionized water was used as the solvent. The mixture was stirred evenly and transferred to a 50 mL polytetrafluoroethylene-lined reactor. The reactor was then placed in a hot air oven and reacted at 240 °C for 24 h. The reactor was then naturally cooled to room temperature to obtain a brown carbon aqueous solution, which was then centrifuged and freeze-dried to obtain carbon dots. (2) 12.0 g of the carbon dots prepared in step (1) were dissolved in 282 mL of EG to obtain an EG-CPDs solution, 700 g of PTA, 30 g of CEPPA, 0.28 g of Sb2O3 and the EG-CPDs solution were added to a polymerization reactor, and the mixture was reacted in a 240° C. incubation environment for 1 h to obtain an oligomer BHET; (3) After the reaction in step (2) was completed, 0.7 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then a polymerization reaction was carried out. The polymerization reaction conditions were as follows: Low vacuum stage: reaction temperature is 270-275°C, reaction time is 0.5h, and system pressure is controlled at -100.80kPa; High vacuum stage: reaction temperature is 276-278°C, reaction time is 3h, and system pressure is controlled at -101.00kPa; After the reaction is completed, a PET composite is obtained, and the carbon point content in the obtained PET composite is 1.5 wt %.
2. A method for preparing a flame retardant polyester composite, characterized in that: (1) Preparation of carbon dots 1.0 g of gelatin was weighed and placed in a 100 mL clean beaker, and 20 mL of deionized water was used as the solvent. The mixture was stirred evenly and transferred to a 50 mL polytetrafluoroethylene-lined reactor. The reactor was then placed in a hot air oven and reacted at 240 °C for 24 h. The reactor was then naturally cooled to room temperature to obtain a brown carbon aqueous solution, which was then centrifuged and freeze-dried to obtain carbon dots. (2) 6.0 g of the carbon dots (CPDs) prepared in step (1) were dissolved in 282 mL of EG to obtain an EG-CPDs solution, 700 g of PTA, 30 g of CEPPA, 0.28 g of Sb2O3 and the EG-CPDs solution were added to a polymerization reactor, and the mixture was reacted at 240° C. for 1 h to obtain an oligomer BHET; (3) After the reaction in step (2) was completed, 0.7 g of anti-hydrolysis agent 1010, 0.65 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then a polymerization reaction was carried out. The polymerization reaction conditions were as follows: Low vacuum stage: reaction temperature is 270-275°C, reaction time is 0.5h, and system pressure is controlled at -100.80kPa; High vacuum stage: reaction temperature is 276-278°C, reaction time is 3h, and system pressure is controlled at -101.00kPa; After the reaction is completed, a PET composite is obtained, and the carbon point content in the obtained PET composite is 0.75wt%.
3. A method for preparing a flame retardant polyester composite, characterized in that: (1) Preparation of carbon dots 1.0 g of gelatin was weighed and placed in a 100 mL clean beaker, and 20 mL of deionized water was used as the solvent. The mixture was stirred evenly and transferred to a 50 mL polytetrafluoroethylene-lined reactor. The reactor was then placed in a hot air oven and reacted at 240 °C for 24 h. The reactor was then naturally cooled to room temperature to obtain a brown carbon aqueous solution, which was then centrifuged and freeze-dried to obtain carbon dots. (2) 8.0 g of the carbon dots (CPDs) prepared in step (1) were dissolved in 282 mL of EG to obtain an EG-CPDs solution, 700 g of PTA, 30 g of CEPPA, 0.28 g of Sb2O3 and the EG-CPDs solution were added to a polymerization reactor, and the mixture was reacted at 240° C. for 1 h to obtain an oligomer BHET; (3) After the reaction in step (2) was completed, 0.70 g of anti-hydrolysis agent 1010, 0.65 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then a polymerization reaction was carried out. The polymerization reaction conditions were as follows: Low vacuum stage: reaction temperature is 270-275°C, reaction time is 0.5h, and system pressure is controlled at -100.80kPa; High vacuum stage: reaction temperature is 276-278°C, reaction time is 3h, and system pressure is controlled at -101.00kPa; After the reaction is completed, a PET composite is obtained, and the carbon point content in the obtained PET composite is 1.00 wt%.
Citation Information
Patent Citations
Compound flame-retardant polyethylene glycol terephthalate system and preparation method thereof
CN105924911A
Preparation method of CDs / TPU fluorescent nanocomposite
CN109504368A
Polyimide composite film containing functionalized carbon quantum dots and preparation method of polyimide composite film
CN109897378A
Carbon quantum dot-polymer composite material, and preparation method and application thereof
CN110819097A